Projeto e desenvolvimento de um sistema de controle e monitoramento de uma unidade de processamento de pinos por atrito portátil - Formoso, Camila Monteiro (2012)
The increased demand in transport and energy industry has led to the search for low cost maintenance techniques. The technique most commonly used is the electric-arc welding. However, it presents a higher cost for use in special environments, and a potential risk to the microstructure of the repaired material. As an alternative, the Friction Repair technique was developed, in which a hole is drilled at the damage area, and filled with a consumable rod submitted to a rotation speed and axial force. Looking forward to applying this technology, the company Petrobras signed an agreement with the Federal University of Uberlandia - Brazil, and a Friction Hydro Pillar Processing Machine was developed. It was used to optimize the parameters and geometries for the new technique. Later, studies for field application began towards designing a portable friction welding head, which is the mechanical part that applies axial load and rotation to the consumable rod. This study aimed to design a new instrumentation and control system to this portable equipment, allowing the performance of friction repais through an automated equipment. Transducers were used for reading the parameters during the tests, and electronic devices were developed for signal conditioning. Additionally, it was adjusted the PID control loops, and a software was developed for data management and monitoring tool during the entire process. Tests were conducted of the various devices used for this project, resulting in the validation of the developed system.